Analisis Perbandingan Umpan Ikan Tembang dan Petek pada Alat Tangkap Bubu terhadap Hasil Tangkapan Kepiting Rajungan di Dermaga Tanjung Kait - Yosep William Ferdinan; Achmad Kusyairi; Alif Astagia (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
One of the issues in fishing culture, particularly in the capture of blue crabs, is the use of improper fishing gear. Using the wrong fishing gear can damage the marine ecosystem. The type of bait used also significantly affects the catch results. Therefore, this study aims to determine the productivity and efficiency of crab traps (bubu) using petek fish and tembang fish as bait to catch blue crabs at the Tanjung Kait Dock, Tangerang, Banten. To assess the efficiency, these two baits were compared using the same fishing gear in the same fishing area, so the most efficient bait for catching blue crabs at the Tanjung Kait Dock, Tangerang, Banten, could be identified. The results of this study show that the type of bait, either petek fish or tembang fish, has an effect on the blue crab catch at the Tanjung Kait Dock. The treatment using petek fish resulted in an average catch of 2.5 kilograms more than the tembang fish.